An analytical correlation for conjugate heat transfer in fin and tube heat exchangers - Kalantari, H. (Elsevier Masson s.r.l., 2021)
Conjugate heat transfer of liquid-gas fin and tube heat exchangers is widely used in industry. However, heat transfer characteristics of such system is difficult to predict as the limiting heat rate can be from either side. This paper aims to quantify the conjugate heat transfer performance of fin and tube heat exchangers via mathematical modeling. Three-dimensional conjugate fluid flow and heat transfer model is developed and validated against the state-of-the-art experimental data and existing analytical correlations. Turbulent k-Îµ model has been employed for the fluid flow and heat transfer modeling. Statistical method, i.e. data reduction and multivariate nonlinear regression techniques, is implemented to analyse the results and to quantify the interaction between parameters. Wide range of parametric studies and simulations is further carried out to evaluate the significance of design, geometrical and operating parameters. According to the results of the study, larger fin length factor and fin pitch and the smaller tube diameter are in favor of fin and tube heat exchangers within the Reynolds number range of 3000â12,000. Finally, a novel conjugate heat transfer correlation for liquid-gas finned tube heat exchangers is proposed to assist engineers for practical designs and applications. The results suggest that our new correlation gives rise to a more accurate conjugate heat transfer prediction as compared to that of traditional non-conjugate counterpart. Â© 2021